Work Discipline and Employee Performance: The Mediating Role of Employee Well-Being - Nuryandi, Tresna; Indiyati, Dian (International Journal of Indonesian Business Review, 2026)
Purpose – This study aims to examine the effects of work discipline and work stress on employee performance through employee well-being as a mediating variable among inbound call center agents of PT Infomedia Nusantara, Telkomsel Bandung service. Methodology/approach – This study employed a quantitative explanatory approach using a survey method. Data were collected through questionnaires distributed to 155 inbound call center agents of PT Infomedia Nusantara selected using simple random sampling techniques. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. Findings – The results indicate that work discipline has a positive and significant effect on employee performance and employee well-being. Employee well-being also has a positive and significant effect on employee performance and partially mediates the relationship between work discipline and employee performance. However, work stress does not have a significant effect on employee well-being or employee performance. Furthermore, employee well-being does not mediate the relationship between work stress and employee performance. Novelty – This study contributes to the human resource management literature by examining the mediating role of employee well-being in the relationship between work discipline, work stress, and employee performance within the Indonesian Business Process Outsourcing (BPO) call center industry. The findings reveal that employee well-being serves as an important psychological mechanism through which work discipline improves employee performance, while work stress appears to have limited influence on employee outcomes in the inbound call center context.